Genetic association of miR-146a, miR-196a2, and miR-499 polymorphisms with hepatocellular carcinoma risk in an Eastern Chinese population - Zhang, Lunjun; Pang, Qing; Wang, Hongtao; Xu, Tao; Ding, Xiaolin (Frontiers in Oncology, 2026)
BackgroundHepatocellular carcinoma (HCC) ranks as the sixth most common cancer and the third leading cause of cancer-related mortality worldwide. MicroRNAs (miRNAs) are known to regulate oncogenic and tumor suppressor pathways, and single nucleotide polymorphisms (SNPs) in miRNAs may influence cancer susceptibility.MethodsWe investigated the association between three miRNA SNPs—miR-146a rs2910164, miR-196a2 rs11614913, and miR-499 rs3746444—and the risk of HCC in an eastern Chinese population. A total of 353 HCC patients and 351 healthy controls were enrolled. Genotyping was performed using PCR-ligase detection reaction (PCR-LDR), and odds ratios (ORs) with 95% confidence intervals (CIs) were calculated.ResultsCompared with the CC genotype, individuals carrying the CT and TT genotypes of miR-196a2 rs11614913 exhibited significantly increased risks of HCC (OR = 1.61, 95% CI: 1.10-2.37; OR: 1.66, 95% CI: 1.07-2.55). The dominant model of miR-196a2 rs11614913 also showed a significant association with HCC risk (P = 0.009). In contrast, carriers of the AG or GG genotype of miR-499 rs3746444 showed a reduced HCC risk (OR = 0.72, 95% CI: 0.52–0.99, P = 0.048). No significant association was found for miR-146a rs2910164 and HCC risk.ConclusionOur findings suggest that miR-196a2 rs11614913 and miR-499 rs3746444 polymorphisms are significantly associated with HCC susceptibility in the eastern Chinese population and may serve as potential genetic biomarkers for early risk assessment.